Parametric contest success functions - Birendra K. Rai; Rajiv Sarin (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The key element of models of contest is the Contest Success Function (CSF) which specifies the winning probabilities of agents. We provide an axiomatization of two parametric families of CSFs. In the first, the winning probability of each agent depends on the investments and a vector of parameters, where each parameter is specific to one of the contestants. In the second, the winning probabilities depend on investments and a scalar parameter common to all contestants.
Keywords: C70; D72; D74; 330; Contest success function; Axiomatization; Rent seeking; Wettbewerb; Nichtkooperatives Spiel; Rent Seeking; Theorie